When cholesterol meets histamine, it gives rise to dendrogenin A: a tumour suppressor metabolite1. (11th April 2016) - Poirot, Marc; Silvente-Poirot, Sandrine
Abstract : Dendrogenin A (DDA) is the first steroidal alkaloid (SA) to be identified in human tissues to date and arises from the stereoselective enzymatic conjugation of 5, 6α-epoxycholesterol (5, 6α-EC) with histamine (HA). DDA induces the re-differentiation of cancer cells in vitro and in vivo and prevents breast cancer (BC) and melanoma development in mice, evidencing its protective role against oncogenesis. In addition, DDA production is lower in BCs compared with normal tissues, suggesting a deregulation of its biosynthesis during carcinogenesis. The discovery of DDA reveals the existence of a new metabolic pathway in mammals which lies at the crossroads of cholesterol and HA metabolism and which leads to the production of this metabolic tumour suppressor.